Washed to the Edges: Renewing the Practice of Footwashing - Zentner-Barrett, Joshua (Studia liturgica, 2023)
The footwashing ritual on Maundy Thursday is often greeted with a mixture of emotions by congregations of all kinds. Neither ordinance nor sacrament, it is one of the more puzzling practices of the church. Its unique appearance in the Gospel of John sets up Jesus’ glorification on the cross—and calls Christians to the same. This paper—in four sections—examines the footwashing as a rite of passage, drawing on the ritual theory of Arnold van Gennep and Victor Turner. The first section offers a study of the theological implications of John 13:1–20. In the second section, these implications are examined in the context of the ritual's liturgical history. The third section introduces certain ritual theories and uses the Johannine passage to exemplify them. Finally, the fourth section discusses this analysis in relation to the church's liturgical practice, specifically its connection to baptism. The relationship between baptism and footwashing offers insights into ways of making the ritual into a transformative, liminal encounter with God, rather than just a performance.